Review: the impact of covid-19 and possible mechanisms on prevention of suicidal ideations - Cho Cho Zaw, Cho Cho Zaw; Mohd Omar, Myat Min (SAS Publishers, 2020)
Covid-19 known as the ‘2019 Novel Coronavirus (2019-nCoV) Pneumonia’ is believed to spread from Wuhan, China, then aroused the global attention due to its fast spread nature throughout the World. In March 2020, World Health Organization (WHO) declared Covid-19 as a global pandemic. Covid-19 causes a tremendous impact to people throughout the world by affecting their physical, mental, social, and financial aspects of their life. Many studies have been pointed out the relationship between stress and suicide, and it is noted that Covid-19 also relates psychological problems among people by making them anxious, stress and worries. Thus, this study is intended to explore the impact of Covid-19, and its relationship with suicidal ideation, and the possible mechanisms to prevent it. The qualitative study by literature review method was used as a methodology. The findings were categorized into two major themes: (i) the impact of Covid-19 and its relationship with suicidal ideation, in which three sub-themes were identified as economic, social, and psychological; and (ii) the possible mechanisms for prevention of suicidal ideation, in which four sub-themes were identified as ‘guidelines on suicide prevention and emergency crisis’, ‘raising awareness regards to suicidal ideation and attempts’, ‘online mental health services for suicide prevention’ and ‘limitation of watching news and social media’. The discussions were made based on the identified information such as the impact of Covid-19, mental health issues and suicidal ideation, preventive measures against suicide including health education, community awareness, online mental health services, government guidelines in preventing suicide, and the national support. The need for further research by using different methodologies was recommended. It is hoped that this paper serves as a source of information for public awareness on suicidal ideation and possible mechanisms to prevent it.